Psychological Capital Predicts Well–Being and Performance in High School Chilean Students - `Carmona-Halty, Marcos; Villegas-Robertson, José Miguel (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2019)
Previous research has emphasized the examination of the role of psychological capital in fostering positive consequences in organizational contexts. However, little evidence has been provided about the role played by this construct in educational contexts. The aim of the study was to examine the predictive role of academic psychological capital in a series of indicators of well–being and an objective measure of performance. Participants were 650 students in Chilean secondary schools. Through the use of structural equations modeling, it was found that academic psychological capital predicts academic engagement, study–related positive emotions, school satisfaction, and academic performance. Theoretical and practical implications of the results are discussed, limitations are addressed, and directions for future research in the school context are proposed.